2016
DOI: 10.1111/dmcn.13333
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of submandibular botulinum neurotoxin A injections on oral motor function in children with drooling due to central nervous system disorders

Abstract: AIM The aims of this study were: (1) to determine the incidence and nature of adverse effects on oral motor function after first injections of botulinum neurotoxin A (BoNT-A) in submandibular glands for excessive drooling in children with central nervous system disorders; and (2) to identify independent predictors of these adverse effects.METHOD A cohort study involved 209 children (123 males, 86 females, aged 4-27y, median 8y 4mo), who received submandibular BoNT-A injections for drooling. Adverse effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…Both procedures were performed as part of day care. BoNT‐A (Botox; Allergan, Dublin, Republic of Ireland) was administered under general anaesthesia, fractioning 1ml over two or three sites throughout the submandibular gland using a Spinocan needle and ultrasound guidance …”
Section: Methodsmentioning
confidence: 99%
“…Both procedures were performed as part of day care. BoNT‐A (Botox; Allergan, Dublin, Republic of Ireland) was administered under general anaesthesia, fractioning 1ml over two or three sites throughout the submandibular gland using a Spinocan needle and ultrasound guidance …”
Section: Methodsmentioning
confidence: 99%
“…BoNT‐A injection in the salivary glands has been said to be effective in reducing respiratory problems in patients with neurological impairment, but further evidence is needed . It should also be taken into account that BoNT‐A injection in the salivary glands can be associated with mild and transient oral motor problems, especially in patients with CP, those with mild drooling before treatment, or if a high dose of BoNT‐A is used . Data about surgical treatments are conflicting.…”
Section: Recurrent Aspirationmentioning
confidence: 99%
“…23,24 It should also be taken into account that BoNT-A injection in the salivary glands can be associated with mild and transient oral motor problems, especially in patients with CP, those with mild drooling before treatment, or if a high dose of BoNT-A is used. 25 Data about surgical treatments are conflicting. Some authors reported that surgical saliva reduction was effective in What this paper adds • Respiratory problems are a significant cause of morbidity in patients with cerebral palsy (CP).…”
Section: Aspiration Of Salivamentioning
confidence: 99%
“…In perioral treatments, only the smallest doses are needed. A slightly higher dosage may lead to difficulties in drinking, whistling and talking [34,35]. Although the maximum dose per treatment session for glabellar lines is 20 U for all sessions combined, the upper dosing limit for the use of botulinum toxin has not been specified.…”
Section: Prevention Of Side Effectsmentioning
confidence: 99%
“…Cyclosporine can induce muscle weakness secondary to neuromuscular blockade, and can lead to respiratory failure. Discontinuing therapy with these drugs or a short cessation is recommended to avoid potential botulinum toxin-related side effects [35][36][37].…”
Section: Prevention Of Side Effectsmentioning
confidence: 99%